Modeling and force control of thin soft McKibben actuator - Faudzi, A. A. M. (Fuji Technology Press, 2016)
This paper presents the modeling of a thin soft McKibben actuator using the system identification (SI) method and its force control. Procedures from the system identification method are used to create a mathematical model (transfer function) from the test data. The autoregressive with exogenous input (ARX)model was chosen as the model structure of the system. Next, a PSO-PID controller was proposed for the force control of the actuator. The simulation data were verified against the test data for the force control using PSOPID and conventional PID. Results showed that the developed model represents the actual system by giving the same characteristics in the force control analysis in step, multi-step, and sinusoidal input.